Clinical Characteristics and Treatment Strategy of Retroperitoneal Schwannoma Adjacent to Important Abdominal Vessels: Three Case Reports and Literature Review - Wu, Qi; Liu, Bingqiang; Lu, Jun; Chang, Hong (Frontiers in Surgery, 2021)
Purpose: The purpose of this study was to review the clinical characteristics and treatment strategies of patients with retroperitoneal schwannomas adjacent to important abdominal vessels. Case Presentation: A total of three patients with retroperitoneal schwannoma immediately adjacent to important blood vessels in the abdominal cavity underwent successful surgical resection. They all had symptoms of abdominal pain and discomfort, two cases underwent three-dimensional reconstruction. There were no serious complications such as peripheral blood vessels and organ damage in all three cases. One case had chyle leakage after surgery, conservative treatment was successfully discharged. Conclusions: Retroperitoneal schwannomas immediately adjacent to important abdominal vessels have unique clinical characteristics. Preoperative three-dimensional reconstruction can fully show the local vascular relationship of the tumor, which is conducive to surgical planning and risk assessment. Benign tumors with large size and adjacent complex vessels can still be completely resected by surgery. Laparotomy resection is safe and feasible.